2022
DOI: 10.1063/5.0091180
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic actuation scheme for nano-kirigami metasurfaces with reconfigurable circular dichroism

Abstract: Nano-kirigami-based deformable metasurfaces offer unique advantages in the dynamic modulation of optical fields and the realization of reconfigurable micro-/nano-optoelectronic devices. Here, we theoretically propose and numerically demonstrate a magnetically actuated deformation scheme for 2D nano-kirigami structures, which can be accurately and continuously transformed from 2D to 3D. Based on the traditional pinwheel structure, an Fe/Au bilayer anti-pinwheel nanostructure is designed and dynamically transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In response, active metamaterials have emerged, which can transform between preprogrammed shapes when subjected to external stimuli, such as mechanical loads, [29][30][31][32] heat, [33][34][35][36] electrical currents, [37][38][39][40] or magnetic fields. [41][42][43][44] These shape transformations often involve internal deformations of the unit cells, which also change the area density and the overall dimensions of the metamaterial. However, a 2D metamaterial covers a specific area.…”
Section: Acousticmentioning
confidence: 99%
“…In response, active metamaterials have emerged, which can transform between preprogrammed shapes when subjected to external stimuli, such as mechanical loads, [29][30][31][32] heat, [33][34][35][36] electrical currents, [37][38][39][40] or magnetic fields. [41][42][43][44] These shape transformations often involve internal deformations of the unit cells, which also change the area density and the overall dimensions of the metamaterial. However, a 2D metamaterial covers a specific area.…”
Section: Acousticmentioning
confidence: 99%
“…In recent years, with the rapid development of micro/nanofabrication technologies, the concept and design of kirigami have been extended to the scientific research in the microscopic world. The key significance lies in that nanoscale kirigami structures (named nano-kirigami) can support integrable 3D morphological transformations upon exposure to external stimuli in microscale, such as mechanical (20), thermal (21), electric (22), and magnetic (23) fields, leading to fundamental breakthroughs and useful applications in biomolecular engineering (24,25), chirality research (26)(27)(28)(29), and nanophotonics (22,27,(29)(30)(31). Therefore, creating versatile nano-kirigami structures with reconfigurable and transformable topology has become a prominent research objective.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, metasurfaces, which are 2D artificial composite meta-atoms, stand out because of their advantageous fabrication process, cost, and capabilities. They feature characteristic electromagnetic (EM) wave-manipulating abilities similar to those of three-dimensional (3D) metamaterials and support a wide spectrum of designed optical responses owing to their comparative flexibility in structural fabrication [6][7][8][9][10][11][12][13][14][15][16][17][18]. Thus, metasurfaces that respond differently to LCP and RCP have emerged as recent academic and industrial hotspots [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that chiroptical responses such as CD and OR can be tuned using tunable chiral metasurfaces [7][8][9][10][11]58,[61][62][63][64][74][75][76][77]. The active modification of chiroptical responses in chiral metasurfaces is attained by external stimuli like electrical fields, magnetic fields, thermal change, or incident light, which changes the properties of individual atoms [58,66].…”
Section: Introductionmentioning
confidence: 99%